Atypical effect of temperature tuning on the insertion of the catalytic iron−sulfur center in a recombinant [FeFe]‐hydrogenase. (24th September 2015) - Morra, Simone; Cordara, Alessandro; Gilardi, Gianfranco; Valetti, Francesca
Abstract: The expression of recombinant [FeFe]‐hydrogenases is an important step for the production of large amount of these enzymes for their exploitation in biotechnology and for the characterization of the protein‐metal cofactor interactions. The correct assembly of the organometallic catalytic site, named H‐cluster, requires a dedicated set of maturases that must be coexpressed in the microbial hosts or used for in vitro assembly of the active enzymes. In this work, the effect of the post‐induction temperature on the recombinant expression of CaHydA [FeFe]‐hydrogenase in E. coli is investigated. The results show a peculiar behavior: the enzyme expression is maximum at lower temperatures (20°C), while the specific activity of the purified CaHydA is higher at higher temperature (30°C), as a consequence of improved protein folding and active site incorporation.